The Effect of Consumer Preference, Perception, and Awareness on Yogurt Purchase Decisions in Banyuwangi Regency - Getta Hayyuning Mangesti; R. Abdoel Djamali; Rizal Rizal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Functional drinks are promoted as products that have health benefits. Yogurt is a functional product that is fortified with calcium, fiber and probiotics. Yogurt imports have increased by 225.98%, this means that it is in line with the increasing need for Indonesian people to consume yogurt. The purpose of this study was (1) to analyse the effect of consumer preferences on yogurt purchasing decisions, (2) to analyse the effect of consumer perceptions on yogurt purchasing decisions, (3) to analyse the effect of consumer awareness on yogurt purchasing decisions. The variables observed in this study were consumer preferences, consumer perceptions, consumer awareness, and purchasing decisions on yogurt. This study uses a quantitative descriptive method. The data obtained were processed using SEM-PLS. Respondents are consumers who often shop at the five modern retailers in the city of Banyuwangi. The results of this study indicate that consumer preferences for yogurt are still considered quite low. Respondents already know that the composition contained in yogurt products is important in deciding to buy. The relationship between consumer perceptions of purchasing decisions is positive. Consumer awareness of purchasing decisions has a significant influence. Respondents already know that yogurt is a healthy fermented milk drink.